Tudor-SN Promotes Early Replication of Dengue Virus in the Aedes aegypti Midgut - Sarah Hélène Merkling; Vincent Raquin; Stéphanie Dabo; Annabelle Henrion-Lacritick; Hervé Blanc; Isabelle Moltini-Conclois; Lionel Frangeul; Hugo Varet; Maria-Carla Saleh; Louis Lambrechts (iScience, 2020)
Summary: Diseases caused by mosquito-borne viruses have been on the rise for the last decades, and novel methods aiming to use laboratory-engineered mosquitoes that are incapable of carrying viruses have been developed to reduce pathogen transmission. This has stimulated efforts to identify optimal target genes that are naturally involved in mosquito antiviral defenses or required for viral replication. Here, we investigated the role of a member of the Tudor protein family, Tudor-SN, upon dengue virus infection in the mosquito Aedes aegypti. Tudor-SN knockdown reduced dengue virus replication in the midgut of Ae. aegypti females. In immunofluorescence assays, Tudor-SN localized to the nucleolus in both Ae. aegypti and Aedes albopictus cells. A reporter assay and small RNA profiling demonstrated that Tudor-SN was not required for RNA interference function in vivo. Collectively, these results defined a novel proviral role for Tudor-SN upon early dengue virus infection of the Ae. aegypti midgut. : Genetics; Virology Subject Areas: Genetics, Virology